A Review on Islamic Corporate Governance Research in Islamic Financial Institution - Izzani Ulfi; Rizaldy, Muhamad Rizky (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2024)
Research development in Islamic corporate governance is way behind the conventional counterpart. This is a call to Muslim scholars to put more attention and effort into the development of Islamic corporate governance through research. This paper aims to be a stimulus in this agenda by developing a research mapping in Islamic corporate governance literature especially within Islamic financial institutions. By employing the bibliometric method, this paper is expected to provide an overview related to the journey of Islamic corporate governance research and future research directions by reviewing 295 articles related to Islamic corporate governance in the Scopus database. The studies used as objects of this research are articles, reviews, and conference papers indexed by the Scopus database and are written in English only, assuming that these articles can represent high-quality research in the field of Islamic corporate governance. Most of the analyzed research was conducted within the scope of Islamic banking, thus, there is a huge demand to do research beyond Islamic banking area such as Islamic insurance and Islamic microfinance. This research will make it easier for researchers to get a comprehensive picture regarding the development of literature in the field of Islamic corporate governance in all Islamic financial institutions.